Leading antenatal classes a practical guide - Priest, Judy; Schott, Judith (Butterworth-Heinemann, 1991)
Practical, down-to-earth and comprehensive, this book offers advice and ideas showing health professionals how to plan, organize, run and evaluate antenatal classes